if the following are true:- instruction #0 is
store src=5 addr=1 imm=1
- the PC at time 0 = 0
- value of cell 1 at time 0 = 3
store src=5 addr=1 imm=1
then value of cell 2 at time 1 = value of cell 2 at time 0
Start from the conclusion and work back up the proof. Click the arrow to show the parents.
- value of cell 2 at time 1 = value of cell 2 at time 0,
if the following are true:
- a = b
- a = c
then b = c
- value of cell 2 at time (0 + 1) = value of cell 2 at time 1,
if 0 + 1 = 1, then value of cell 2 at time (0 + 1) = value of cell 2 at time 1
- 0 + 1 = 1, 0 + a = a
- value of cell 2 at time (0 + 1) = value of cell 2 at time 0,
if the following are true:
- instruction #i is
store src=src addr=addr imm=imm
- the PC at time t = i
- not (other = (value of cell addr at time t) + imm)
then value of cell other at time (t + 1) = value of cell other at time t
- instruction #0 is
store src=5 addr=1 imm=1
- the PC at time 0 = 0
- not (2 = (value of cell 1 at time 0) + 1),
if the following are true:
- a
- b = a
then b
- not (2 = 4), not (2 = 4)
- not (2 = (value of cell 1 at time 0) + 1) = not (2 = 4),
if 2 = (value of cell 1 at time 0) + 1 = 2 = 4, then not (2 = (value of cell 1 at time 0) + 1) = not (2 = 4)
- 2 = (value of cell 1 at time 0) + 1 = 2 = 4,
if (value of cell 1 at time 0) + 1 = 4, then 2 = (value of cell 1 at time 0) + 1 = 2 = 4
- (value of cell 1 at time 0) + 1 = 4,
if the following are true:
- a = b
- b = c
then a = c
- (value of cell 1 at time 0) + 1 = 3 + 1,
if value of cell 1 at time 0 = 3, then (value of cell 1 at time 0) + 1 = 3 + 1
- value of cell 1 at time 0 = 3
- 3 + 1 = 4, 3 + 1 = 4
- (value of cell 1 at time 0) + 1 = 4,
- 2 = (value of cell 1 at time 0) + 1 = 2 = 4,
- instruction #i is